Microfluidics for Cells and Other Organisms - van Noort, Danny (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Microfluidics-based devices play an important role in creating realistic microenvironments in which cell cultures can thrive. They can, for example, be used to monitor drug toxicity and perform medical diagnostics, and be in a static-, perfusion- or droplet-based device. They can also be used to study cell-cell, cell-matrix or cell-surface interactions. Cells can be either single cells, 3D cell cultures or co-cultures. Other organisms could include bacteria, zebra fish embryo, C. elegans, to name a few.